Thai General Election 2019 : Regime Change or Consolidation? - Antonio L Rappa (2018)
Thai Prime Minister Prayut Chan-o-Cha has announced that the general election will be held by February 2019 if three conditions are met. Why is Prayut demanding three conditions and to what extent will the GE result in political change or consolidation for the incumbent Thai junta?